Analysis of glucocerebrosidase gene mutations in Iranian patients with Gaucher disease: Identification of 6 novel mutations - Mozafari, Hadi; Taghikhani, Mohammad; Rahimi, Zohreh; Vaisi-Raygani, Asad; Ansari, Shahla; Khatami, Shohreh; Alaei, Mohammadreza; Saghiri, Reza (Iranian Journal of Child Neurology, 2021)
Abstract Objective Gaucher disease (GD) is the most common autosomal recessive disorder of glycolipid storage. It results from mutations in the glucocerebrosidase (GBA) gene and leads to GBA deficiency. Different mutations are associated with different phenotypes in the three major types of GD. Materials & Methods The spectrum of mutations in GBA gene in 26 unrelated patients with GD from different Iranian populations was determined by DNA sequencing, polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP), and amplification-refractory mutation system (ARMS) methods. An in silico analysis was also performed for novel mutations Results Six new mutations were identified in this study. The newly detected mutations that could be theoretically harmful included p.I200T (c.599T>C), p.H312D (c.934C>G), p.L325S (c.974T>C), p.L393V (c.1177C>G), p.S439G (c.1315A>G), and p.M455R (c.1365G>A). Also, p.L483P, p.N409S, p.W420X, p.E379K, p.R398Q, p.N227S, p.R202Q, and p.D448H mutations were identified in the patients. Besides, two new complex mutations, namely, p.S439G/p.S439G+p. E379K/- and p.R202Q/p.R202Q+p.N227S/p.N227S, were detected. The most common GBA mutation in the population was p.L483P with an allele frequency of 32.7%, followed by p.N409S (19.2%). Conclusion The present study detected six new mutations of GBA gene among GD patients. Two mutations (p.L483P and p.N409S) were especially common among Iranians; this finding can be used in implementing screening programs and understanding the molecular basis of GD.